Correcting Ski Resort Trajectories Extracted from Video - Buchuan Zhang; Andreas Schadschneider (Applied Sciences)
Accidents at ski resorts present a significant safety concern, underscoring the urgency of addressing these issues. This study aims to enhance safety protocols by providing resort operators with more effective data analysis methodologies. We present and test methods for analyzing video footage from downhill ski areas where detailed information needed to correct errors, due to perspective, lens distortion, etc., is not available. This can be the case, e.g., for webcam footage and accidental videos (e.g., on YouTube). As much of this kind of video is available and could be used for statistical analysis, methods are needed that allow for at least for an approximate consideration of such aspects. Using video footage obtained from various ski resorts, we developed and tested several methods for analyzing and correcting the trajectories of skiers captured in the videos. Our analysis revealed that using five reference lines, along with the most appropriate x and y coordinate corrections, is an effective approach for achieving precise calibration of the video data. The corrected trajectory data, adjusted for perspective distortions and scaling inaccuracies, provide a detailed basis for analyzing skier behavior and identifying high-risk zones prone to collisions.